2014
DOI: 10.5070/v426110430
|View full text |Cite
|
Sign up to set email alerts
|

Sprague Dawley Female Rat Consumption of a Liquid Bait Containing Vinylcyclohexene Diepoxide and Triptolide Leads to Subfertility

Abstract: Worldwide, Norway rats cause significant infrastructure damage, agricultural losses, and carry zoonotic diseases.Due to rat fecundity, killing them by mechanical and/or poison does not lead to sustainable management of their populations. Our biotechnology company, SenesTech, Inc, has developed an environmentally safe oral bait taken by rats, causing them to produce fewer rat pups and take longer to deliver, without any observable adverse effects. The fertility control bait is an emulsion and contains two chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Studies have also demonstrated a reduction in litter sizes in the first breeding round with baited females and unbaited males (Dyer and Mayer 2014). A more recent study showed males and females consumed approximately 4% and 10% of their body weight, respectively, and no females delivered litters in the first breeding round (Dyer and Mayer 2014). These results confirm FMB is palatable to Sprague Dawley rats and effective in reducing litter size; however, these results can only suggest how wild rats might respond to FMB.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Studies have also demonstrated a reduction in litter sizes in the first breeding round with baited females and unbaited males (Dyer and Mayer 2014). A more recent study showed males and females consumed approximately 4% and 10% of their body weight, respectively, and no females delivered litters in the first breeding round (Dyer and Mayer 2014). These results confirm FMB is palatable to Sprague Dawley rats and effective in reducing litter size; however, these results can only suggest how wild rats might respond to FMB.…”
Section: Introductionmentioning
confidence: 91%
“…In males, FMB targets the number of epididymal sperm and sperm mobility (Liu et al 2010, Xu andZhao 2010). Laboratory studies have confirmed that FMB is highly palatable; both sexes will consume approximately 10% of their body weight while in the presence of ad libitum rodent chow and water (Dyer and Mayer 2014). Studies have also demonstrated a reduction in litter sizes in the first breeding round with baited females and unbaited males (Dyer and Mayer 2014).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This outcome has already been observed in the case of resistance to warfarin(Rost et al, 2009), but may also be problematic with new control methods. For example, many cities have conducted experimental trials of chemical sterilization baits that operate on both males and females(Dyer & Mayer, 2014). Such strong selection acting directly on reproduction could favor individuals with heritable bait aversion and/or biochemical resistance to the compound.Population genetic analyses have also played a role in understanding commensal rodent movements and spatial extent of rat populations, with many potential applications to better target pest management efforts.…”
mentioning
confidence: 99%